Fungal Biofilms 2020 - Rodrigues, Célia F.; Romo, Jesus A. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Fungal infections are an important and increasing global threat, carrying not only high morbidity and mortality rates, but also high healthcare costs. Without an effective response, it is predicted that 10 million people will die per year as a result of multi-drug-resistant pathogens. A high percentage of the mortalities caused by fungi are known to be biofilm-related.This Special Issue, "Fungal Biofilms 2020", is intended to cover the state of fungal biofilm research, from virulence and pathogenicity, to new compounds with antibiofilm and antifungal activity. We welcome reviews and original research articles covering the development/evaluation/validation of recent studies, especially those regarding multidrug resistance.